PENGARUH PEMBERIAN PUPUK ORGANIK CAIR LIDAH BUAYA (Aloe vera) TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea canephora,Pierre) - Muhardi, Muhardi; Syafrinal, Syafrinal; Yulia, Arnis En (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The objective of this research is to determine the effect of giving Aloe Vera Biofertilizer Liquid and to get the best concentration to increase the growth of Robusta coffee seeds. This research was conducted at experimental station of the Faculty of Agriculture, Riau University. This research was conducted experimentally using a Completely Randomized Design consisting of five treatments and four replications. The treatment in this study was the treatment without Aloe Vera Biofertilizer Liquid, Aloe Vera Biofertilizer Liquid concentration 5 ml.l-1 air, 10 ml.l-1 air, 15 ml.l-1 air and 20 ml.l-1 air. The data obtained were analyzed by variance and tested further with Duncan new range test at the level of 5 %. The observed parameters were increase in plant height (cm), increase in stem base circumference (cm), increase in number of leaves (strands) and leaf area (cm2). The results showed that the application of Aloe Vera Biofertilizer Liquid with a concentration of 20 ml.l-1 air is the best concentration in increasing the growth of Robusta coffee seeds. Keywords :Coffee Seed, Aloe Vera Biofertilizer